Perempuan dalam Dunia kuliner di Kawasan Wisata Tanggo Rajo Jambi - Siti Heidi Karmela; Ferry Yanto (Jurnal Ilmiah Dikdaya, 2023)
: This research is historical research with the theme of women's history which examines the involvement, role, and contribution of women in the non-formal economic sector, namely those who become culinary traders in the Tanggo Rajo Ancol Tourism Area, Jambi. Meanwhile, the research method is historical method by following the stages of heuristics, criticism, interpretation, and historiography. The conclusions of the research show that women who become culinary traders in this tourist area successfully carry out their dual roles both in the domestic, household and public sectors. In the domestic sector, they have succeeded in acting as housewives who take care of and serve the needs of their husbands and children, while in the public sector they can generate their own money from selling various kinds of culinary delights in the Tanggo Rajo Ancol Tourism Area, Jambi. The findings of the study show that women culinary traders in the Tanggo Rajo Ancol Tourism Area, Jambi, have been selling for decades before the area became known as a tourist area. Furthermore, it is known that the income of culinary traders will increase compared to their daily income if it coincides with important moments such as school holidays, the month of Ramadan, holidays, celebrations of the Indonesian Independence Day and Jambi Province Anniversary, and festivals with cultural nuances. Next, culinary traders in the Tanggo Rajo Ancol Jambi Tourism Area are concentrated in two locations, namely under the Gentala Arasy Bridge to the Tanggo Rajo Gate and from the Jambi Police Chief's House to Kasang Port / Pasir Harbor